The TECHNIQUE OF MANUFACTURE AND VALUES OF SIMPLICIA AND ETHANOL EXTRACT OF BAGORE (Caesalpinia crista L.) SEEDS ORIGINAL POLEWALI MANDAR - Rafiah Arsyad (PHARMACY UMI JOURNAL SYSTEM, 2023)
Introduction : Simplicia and extracts are raw materials for making traditional medicines. One of the traditional medicines often used by the people of Polewali Mandar is bagore seeds (Caesalpinia crista). The purpose of this study was to find out how to make simplicia and bagore seed extract (EBB) and their yield values. Research method: laboratory experimental. Bagore seed simplicia is weighed for its wet weight and then made by drying. Dried simplicia is pollinated and given a container and label, before being stored or processed further. Furthermore, the simplicia powder was extracted by maceration method using 70% ethanol solvent for 3x24 hours at room temperature. The maserate is separated from the residue, and the residue is re-macerated until the solvent is clear. The maserate was evaporated with a rotary evaporator at 10°C below the boiling point of the solvent until the extract was concentrated, and evaporation was continued in a water bath at 60°C, until the extract was thick. Simplicia and extracts obtained were calculated for their respective yield values. The results of the study: the results of making simplicia obtained the yield value of 20% of bagore seeds, and the value of the macerated EBB yield was 13.66%. Conclusion: Methods of manufacture and yield values ​​of simplicia and extracts serve as a reference in the manufacture of pharmaceutical raw materials for scientifically approved traditional medicines.